Workplace flexibility and organisational citizenship behaviour: An investigation of the mediating role of engagement and moderating role of perceived fairness - Koon, Vui Yee*; Chong, Kai Ni (InderScience Publishers, 2018)
This study aims to better understand the effect of employee engagement and perceived fairness on positive workplace behaviour. Using the social exchange theory (SET) and agent-system model, this study investigated: 1) the mediating role of employee engagement in linking workplace flexibility with organisational citizenship behaviour (OCB); 2) the moderating role of perceived fairness in influencing the mediation. The conceptual model and defined hypotheses were measured using hierarchical multiple regression, different mediation approaches, and Edwards and Lambert's (2007) moderated mediation analysis. Aiken and West's (1991) simple slope test was used to illustrate the moderation effect of perceived fairness. The findings suggest that workplace flexibility was significantly related to OCB with employee engagement serving as a partial mediator. Perceived fairness moderated the mediating relationship but a stronger effect was found for low perceived fairness than for high perceived fairness. Findings from this study imply the necessity of creating flexibility in the workplace for positive employee behaviours